PENGARUH DISIPLIN KERJA DALAM MENINGKATKAN PRODUKTIVITAS KERJA MELALUI MOTIVASI KERJA KARYAWAN PT. SINARMAS ASSET MANAGEMENT - Nadya Salsyabilla; Edy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
Purpose to determine the influence of work discipline on work productivity PT. Sinarmas Asset Managamenet through work motivation. This research uses quantitative methods. This research uses a quantitative approach. The sampling technique in this research uses a saturated sample type. The data analysis method uses path analysis. The research results can be concluded as follows: 1). Work discipline directly has a significant effect on work productivity. 2). Work motivation directly has a significant effect on work productivity. 3). Work discipline directly has a significant effect on work motivation. 4). Indirectly, Work discipline has no effect on work productivity of productivity PT. Sinarmas Asset Managamenet through work motivation.